Corruption Perception and Religiosity: Examining Their Effects on Tax Evasion - Rosalita Rachma` Agusti; Mutia Rahma Putri (Jurnal Ilmiah Akuntansi, 2026)
This study examines how perceptions of tax corruption influence tax evasion among individual taxpayers in Tangerang, Indonesia, with religiosity positioned as a moderating variable. Unlike prior studies that treat religiosity as a direct determinant of compliance, this study repositions it as a conditional moderator, a theoretical configuration that remains underexplored in developing country contexts. Integrating Social Contract Theory and Social Control Theory into a unified framework, survey data from 404 taxpayers were analyzed using PLS-SEM. Results confirm a significant positive effect of corruption perception on tax evasion, while religiosity does not significantly moderate this relationship. These findings suggest that institutional integrity plays a more decisive role than religious or moral appeals in shaping compliance, underscoring the need for systemic anti-corruption efforts alongside values-based campaigns.